Diffraction‐Unlimited Fluorescence Microscopy of Living Biological Samples Using pcSOFI. Issue 1 (2nd March 2015) - Duwé, Sam; Moeyaert, Benjamien; Dedecker, Peter
Abstract: The complex microscopic nature of many live biological processes is often obscured by the diffraction limit of light, requiring diffraction‐unlimited fluorescence microscopy to resolve them. Because of the vast range of different processes that can be studied, sub‐diffraction imaging should work efficiently under many different conditions. Photochromic stochastic optical fluctuation imaging (pcSOFI) is a recent addition to the field of diffraction‐unlimited fluorescence microscopy. This robust and versatile method employs a statistical analysis of random fluctuations in the emission of single labels, in this case reversibly switchable fluorescent proteins (RSFPs), to retrieve super‐resolution information. Added to the resolution enhancement, pcSOFI also offers contrast enhancement and background reduction in a practical and convenient way. Here, we describe the necessary steps to obtain diffraction‐unlimited images, including multicolor and three‐dimensional imaging, and highlight the advantages of pcSOFI together with the circumstances under which pcSOFI can be favorably applied. © 2015 by John Wiley & Sons, Inc.